Work Demands, Independence, Valuation as a Farmer, and Mental Health in Farming. A Study of Mental Health Among Dairy Farmers and Vegetable- And Potato Farmers in Norway - Logstein Brit (European Countryside, 2021)
In this study, the aim was to advance the knowledge about mental health status in the Norwegian farming population. Based on the dimensions in the Job Demand and Control model (Karasek, 1979); work demands and control, and the importance of recognition and dignity (Andrew Sayer, 2011), the aim was to study the effects of work demands, sense of independence and valuation on mental health status among farmers. It included an assessment of how the sectorial level, the sectors of dairy production and vegetable- and potato production, explains farmers` mental health status. A postal survey was conducted in 2012 using a structured questionnaire, and I included farmers from two sectors in the Norwegian agriculture: dairy farming (n = 493) and vegetable and potato farming (n = 122). The analyses were carried out by multigroup structural equation modeling (SEM). This study concludes that low work demands in farming, strong sense of independence as a farmer, and farmers` perception of valuation associate with good mental health. The mental health status in dairy farmers and vegetable and potato farmers and the effects of work demands, sense of independence and valuation on mental health status, were equal across groups.